Ocular involvement in childhood leukemias - Soylu, Merih; Tanyeli, Atilla; Özdemir, Nusret; Eroğlu, Adem; Ersöz, T. Reha (The Turkish Journal of Pediatrics, 1994)
Ocular involvement was detected in 36 of 84 children suffering from acute leukemia. The major manifestation of leukemic ophthalmopathy was retinal hemorrhage. Neither platelet counts nor hematocrit values correlated with the occurrence of hemorrhages. As the eye is a pharmacologic sanctuary, it is emphasized that full ophthalmologic evaluation of leukemic patients is a critical part of their follow-up and will guide the choice of therapeutic regimen.
Keywords: childhood leukemias; ocular involvement; retinal hemorrhages; optic nerve involvement; local radiotherapy